Cross-sectional use of barcode of life data system and GenBank as DNA barcoding databases for the advancement of museomics - Nakazato, Takeru; Jinbo, Utsugi (Frontiers in Ecology and Evolution, 2022)
Museomics is an approach to the DNA sequencing of museum specimens that can generate both biodiversity and sequence information. In this study, we surveyed both the biodiversity information-based database BOLD (Barcode of Life System) and the sequence information database GenBank, by using DNA barcoding data as an example, with the aim of integrating the data from these two databases. DNA barcoding is a method of identifying species from DNA sequences by using short genetic markers. We surveyed how many entries had biodiversity information (such as links to BOLD and specimen IDs) by downloading all fish, insect, and flowering plant data available from the GenBank Nucleotide, and BOLD ID was assigned to 26.2% of entries for insects. In the same way, we downloaded the respective BOLD data and checked the status of links to sequence information. We also investigated how many species do these databases cover, and 7,693 species were found to exist only in BOLD. In the future, as museomics develops as a field, the targeted sequences will be extended not only to DNA barcodes, but also to mitochondrial genomes, other genes, and genome sequences. Consequently, the value of the sequence data will increase. In addition, various species will be sequenced and, thus, biodiversity information such as the evidence specimen photographs used as a basis for species identification, will become even more indispensable. This study contributes to the acceleration of museomics-associated research by using databases in a cross-sectional manner.